2022
DOI: 10.1021/acsomega.1c06967
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Study on Mefenamic Acid Polymorphic Forms

Abstract: Three polymorphic structures of mefenamic acid, which is a very popular drug, have been studied using quantum chemical methods. It has been shown that the centrosymmetric dimer formed due to two O–H···O hydrogen bonds is a complex building unit in all of the polymorphic structures under study. On the basis of an analysis of the pairwise interaction energies between molecules, the polymorphic forms I and II are classified as columnar-layered while the polymorphic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Therefore, the question of their behavior under mechanical stress or pressure is of great practical importance. To estimate the possibility of a polymorphic transition under external influence in these metastable polymorphic forms, the method proposed earlier was applied. The results of the study of pairwise interaction energies in metastable polymorphic forms can be used to determine a possible way of the crystal structure deformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the question of their behavior under mechanical stress or pressure is of great practical importance. To estimate the possibility of a polymorphic transition under external influence in these metastable polymorphic forms, the method proposed earlier was applied. The results of the study of pairwise interaction energies in metastable polymorphic forms can be used to determine a possible way of the crystal structure deformation.…”
Section: Resultsmentioning
confidence: 99%
“…For modeling the shear deformation possibility, DBU 0 (mobile part) and a fragment of the neighboring layer (fixed part) were extracted from the crystal structure. , The displacement of the mobile part in relation to the fixed part on one crystallographic translation in two directions within the layer fragment was performed with the step size equal to 1/100 of a translation. The minimal interatomic distances between molecules of the mobile and fixed parts were calculated at each point of the displacement.…”
Section: Methodsmentioning
confidence: 99%
“…Such a polymorphic transition looks to be useful in the case of concomitant polymorphs accidentally produced in the pharmaceutical industry. Taking into account the potential biological properties of the 2-iminocoumarin-3-carboxamide, the possibility of a polymorphic transition under external factors for the polymorphic crystals of 1m and 1t was assessed using quantum chemical modeling according to the method proposed earlier (Vaksler et al, 2021;Shishkina et al, 2022).…”
Section: Interactionmentioning
confidence: 99%
“…Modeling of shear deformation. For modeling of the shear deformation possibility, the two-step methodology based on the movement of one building unit (a mobile part) with respect to a fragment of one neighboring layer (a fixed part) was applied (Vaksler et al, 2021;Shishkina et al, 2022).…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Recently, it has been found that (NSAID) can be used to treat musculosketal pain. An important aspect in the literature is that prepared many Mefenamic acid derivatives containing heterocyclic moiety, which have been useful in medicine and cytotoxic activities [5][6][7]. Various synthetic routes to 1,3-Oxazepine derivatives have been synthesised based on different strategies for the construction of the heterocyclic ring [8][9][10].…”
Section: Introductionmentioning
confidence: 99%